The Moor for the Malayali Masses: A Study of "Othello" in "Kathaprasangam" - Thomas, Sanju (Multicultural Shakespeare: Translation, Appropriation and Performance, 2016)
Shakespeare, undoubtedly, has been one of the most important Western influences on Malayalam literature. His works have inspired themes of classical art forms like kathakali and popular art forms like kathaprasangam. A secular story telling art form of Kerala, kathaprasangam is a derivative of the classical art form, harikatha. It was widely used to create an interest in modern Malayalam literature and was often used as a vehicle of social, political propaganda. The story is told by a single narrator who masquerades as the characters, and also dons the mantle of an interpreter and a commentator. Thus, there is immense scope for the artist to rewrite, subvert and manipulate the story. The paper explores V. Sambasivan’s adaptation of Othello in kathaprasangam to bring out the transformation the text undergoes to suit the cultural context, the target audience and the time-frame of the performance. The text undergoes alteration at different levels—from English language to Malayalam, from verse to prose, from high culture to popular art. The paper aims at understanding how a story set in a different time and distant place converses with the essential local milieu through selective suppression, adaptation and appropriation.